A rare case of young multiple myeloma - Chinnasamy, Vignesh; K., Mahendra Kumar; M., Jagadeesan; Karthik S., Prasanna (International Journal of Advances in Medicine, 2022)
Multiple myeloma arises from a clonal population of plasma cells. It accounts for approximately 10% of all hematologic malignancies. It is a disease of the elderly and extremely rare in those under 50 years of age. Multiple myeloma is a malignancy of immune cells. The immune cells involved in tumorigenesis are especially plasma cells. The presentation may vary drastically in patients with this disease. The disease presentation ranges from an asymptomatic variant called Monoclonal gammopathy of unknown significance to a severe form of full-fledged multiple myeloma with systemic manifestations. The disease usually affects people aged more than 50. Here, we report a 40-year-old male who presented with anemia, and on further workup, he was diagnosed with multiple myeloma.